Peningkatan Pengetahuan dan Keterampilan PHBS Sebagai Upaya Pencegahan Pandemi Covid-19 Dengan Media Video Interaktif di Yayasan Al-Kahfi Surakarta - Nabilatul Fanny; Yunita Wisda Tumarta Arif; Laila Nur Azizah (Duta Abdimas, 2022)
The Al-Kahfi Foundation is a social institution engaged in education and charity. The results of the preliminary survey conducted through observation and interviews with foundation administrators found that there were problems controlling children's behavior towards personal health, especially those who still lived with their families. The results of a survey of 10 orphanage children showed that as many as 40% of children had insufficient knowledge and did not understand the importance of having a clean and healthy lifestyle (PHBS), and 50% of children did not clearly understand what Covid-19 was and the dangers of the virus. The purpose of this activity is to increase PHBS knowledge and skills; Increase participants' awareness of the importance of preventing the dangers arising from the Covid-19 disease; Increase the willingness and ability of participants to prevent themselves from the dangers of Covid-19. The media used to support these community service activities are: Videos, screening of documentary films about smoking; Power Point about the extension material includes; LCD; Pre-test and post-test sheets. While the methods used are lectures, discussions, and questions and answers. Extension was carried out both verbally and by video playback. The PHBS video screening is intended to provide information on how to wash hands and wear masks properly and correctly, cough etiquette, maintain balanced nutrition, and carry out social distancing. Playing motion pictures is the method chosen so that the steps in preventing Covid-19 are more interesting and can be easily remembered by children and adolescents, so that their implementation is faster. Based on the results of outreach activities, it is known that counseling using the visual method or video playback takes a person's attention more than the lecture method.